PENGELOLAAN ARSIP DI ERA TEKNOLOGI INFORMASI - Hakim, Triono Dul (Jurnal Ilmu Budaya, 2015)
The using of digital/ electronic information is a trend in this era of globalization and information technology. The role of digital archieve supports both private and government institutions from various aspects (commercial institutional and functional ones). There are some elements needed to manage an archieve such as human resource, hard and software and a room. Digital achieve can reduce papers, printed ink. It can also reduce time to access data, human resources and the possibility of data destroying. To be optimal, archieve management should be handled professionally. For that reason, the management needs those who understandthe philosophy and usage of archieve and those who master information technology.